The Role of Sodium in Diabetic Cardiomyopathy - Doliba, Nicolai M.; Babsky, Andriy M.; Osbakken, Mary D. (Frontiers in Physiology, 2018)
Cardiovascular complications are the major cause of mortality and morbidity in diabetic patients. The changes in myocardial structure and function associated with diabetes are collectively called diabetic cardiomyopathy. Numerous molecular mechanisms have been proposed that could contribute to the development of diabetic cardiomyopathy and have been studied in various animal models of type 1 or type 2 diabetes. The current review focuses on the role of sodium (Na+) in diabetic cardiomyopathy and provides unique data on the linkage between Na+ flux and energy metabolism, studied with non-invasive 23Na, and 31P-NMR Spectroscopy, polarography and mass spectroscopy. 23Na NMR studies allow determination of the intracellular and extracellular Na+ pools by splitting the total Na+ peak into 2 resonances after the addition of a shift reagent to the perfusate. Using this technology, we found that intracellular Na+ is approximately two times higher in diabetic cardiomyocytes than in control possibly due to combined changes in the activity of Na+-K+ pump, Na+/H+ exchanger 1 (NHE1) and Na+-glucose cotransporter. We hypothesized that the increase in Na+ activates the mitochondrial membrane Na+/Ca2+ exchanger, which leads to a loss of intramitochondrial Ca2+, with a subsequent alteration in mitochondrial bioenergetics and function. Using isolated mitochondria we showed that the addition of Na+ (1-10 mM) led to a dose-dependent decrease in oxidative phosphorylation and that this effect was reversed by providing extramitochondrial Ca2+ or by inhibiting the mitochondrial Na+/Ca2+ exchanger with diltiazem. Similar experiments with 31P-NMR in isolated superfused mitochondria embedded in agarose beads showed that Na+ (3-30 mM) led to significantly decreased ATP levels and that this effect was stronger in diabetic rats. These data suggest that in diabetic cardiomyocytes, increased Na+ leads to abnormalities in oxidative phosphorylation and a subsequent decrease in ATP levels. In support of these data, using 31P-NMR we showed that the baseline betaATP and phosphocreatine (PCr) were lower in diabetic cardiomyocytes than in control, suggesting that diabetic cardiomyocytes have depressed bioenergetic function. Thus, both altered intracellular Na+ levels and bioenergetics and their interactions may significantly contribute to the pathology of diabetic cardiomyopathy.